The effect of sintering parameters on the mechanical properties and hydrothermal ageing resistance of Y-TZP Ceramic / Sutharsini Ubenthiran - Ubenthiran, Sutharsini (2015)
Achieving high density and uniform fine grain size distribution are two of the most essential goals in the sintering of zirconia ceramics, which enhance the hydrothermal ageing resistance and mechanical properties such as hardness and fracture toughness of the ceramics. Two step sintering method (TSS) is one of the most promising approach to achieve high densification with fine grain microstructure. In this study, single step sintering (SSS) and two step sintering were applied to evaluate the suitable selection of sintering parameters such as sintering temperature and time to enhance the hydrothermal ageing resistance of 3 mol% yttria stabilised tetragonal zirconia polycrystals (3Y-TZP) ceramics. In the SSS, as the sintering temperature is decreased, grain growth is controlled and the surface yttria concentration is increased. As a result, hydrothermal ageing resistance is enhanced however, density of the as sintered ceramics was strongly dependent on temperature and it decreased with decreasing sintering temperature. The 3Y-TZP ceramics sintered with TSS at 1400°C for 1 min. and 1200°C for 4 hours and above at first and second step sintering, respectively exhibited ultrafine grain size (~250 nm) and optimum surface yttria concentration (>2.5 mol%) hence they revealed excellent hydrothermal ageing resistance. As the second step sintering time was increased, surface yttria concentration was found to increase hence the hydrothermal ageing resistance was enhanced. The sample sintered for 20 hours and above did not exhibit any phase transformation even after 100 hours of hydrothermal ageing. The ageing study showed that the destabilisation of the tetragonal phase was associated with the leaching of yttria stabiliser during hydrothermal ageing, hence triggering the monoclinic phase formation. The volume expansion associated with tetragonal to monoclinic phase transformation initiates microcracking through grain boundary. Consequently, microcracks coalesce and develops macrocrack which eventually results in catastrophic failure of the zirconia body. The 3Y-TZP ceramics sintered with TSS at 1400°C for 1 min and 1200°C for 1 hours and above at first and second step sintering, respectively exhibited high density ( 96%), hardness (>11 GPa), fracture toughness (~5MPam1/2), and Young’s modulus (~200 GPa). As the first step sintering temperature increased from 1400 to 1500°C, density and fracture toughness were increased. On the other hand, grain size was also increased but was accompanied by a decrease in the surface yttria concentration. This in turn reducing the hydrothermal ageing resistance of the ceramic. As the second step sintering temperature was increased from 1200 to 1300°C, density and hardness increased however, hydrothermal ageing resistance was decreased. Implementation of TSS method for 3Y-TZP ceramics enhanced the hydrothermal ageing resistance. 3Y-TZP ceramics sintered at first step sintering temperature 1400°C for 1 min. and second step sintering temperature 1200°C for 20 hours and above were not susceptible to hydrothermal ageing at 180°C and 10 bar up to 100 hours.